Effect of Steam Cooking on Quality Characteristics of Shelf Stable Chicken Pickle - Singh, Shubha; Goswami, Meena; Pathak, Vikas; Verma, Arun Kumar; V, Rajkumar (Journal of Meat Science, 2019)
The present study was carried out to evaluate the effect of stream cooking (without pressure) on quality characteristics of shelf stable chicken pickle. Chicken pickle was prepared as per method, prescribed by Das et al. (2013) with slight modifications. An attempt was made to improve the quality characteristics of chicken pickle by precooking of marinated meat by steam cooking without pressure for 10, 15 and 20 minutes separately. There was a significant difference (P<0.05) among the treatments for all physico-chemical properties, except fat and ash content. The pH, moisture content and water activity values increased significantly (P<0.05) while titratable acidity and protein content decreased significantly (P<0.05) with increased precooking time. Among the colour and textural parameters, light ness (L*) and shear force values decreased significantly (P<0.05) while there were no significant difference in redness (a*) and yellowness (b*). Sensory scores were not significantly affected with respect to color and appearance, saltiness and sourness however flavour, texture, juiciness and overall acceptability scores were significantly (P<0.05) higher in precooking of marinated meat for 15 minutes. It can be concluded that the best quality chicken pickle could be prepared with pre-cooking of marinated chicken meat by steam cooking (without pressure) for 15 minutes in terms of juiciness, texture and tenderness.